Minimally invasive chevron/akin osteotomy: radiographic outcomes - Carvalho, Kepler Alencar Mendes de; Torrico, Fernando Garnica; Oliveira, David Satiro Borges Pereira de; Baptista, André Donato (Journal of the Foot & Ankle, 2021)
Objective: To evaluate radiographic outcomes in patients undergoing minimally invasive Chevron/Akin osteotomy (MICA) for hallux valgus correction. Methods: We have treated 31 patients (40 feet). Preoperative and postoperative hallux metatarsophalangeal angles (hallux valgus angles, HVA), intermetatarsal angles (IMA) between the first and second metatarsals, and distal metatarsal articular angles (DMAA) were followed up for 12 months. Results: The mean age of the patients was 53.2 years. Mean preoperative HVA, IMA, and DMAA values were 28.85°, 15.38°, and 14.35°, respectively. The mean postoperative angles measured after 1 year were 10.60°, 7.95°, and 7.48°. Improvements in HVA, IMA, and DMAA values showed statistical relevance. There were no losses in angular parameters during follow-up. Conclusion: The radiographic outcomes in patients undergoing MICA osteotomy for hallux valgus correction followed up for 12 months showed significant improvements and no recurrence of the deformity. Our results suggest that this technique is effective for correcting hallux valgus. Level of Evidence III; Therapeutic Studies; Comparative Retrospective Study.